Immunohistochemical Evaluation of TGF-ß Isoforms in Cases with Ovarian Endometriosis and Follicular Cyst - Şentaş, Abdulmuttalip; İnal, Murat; Sancı, Muzaffer; Yıldırım, Yusuf; İnan, Sevinç; Vatansever, Seda; Dicle, Nilgün; İspahi, Çiğdem (Gynecology Obstetrics & Reproductive Medicine, 2007)
OBJECTIVE: To evaluate the distribution of Transforming Growth Factor (TGF)-ß1, ß2 and ß3 in surgical specimens of the cases with endometriosis and follicular cysts. STUDY DESIGN: This prospective clinical study was carried out at Aegean Obstetrics and Gynecology Training and Research Hospital, a tertiary referral center. A total of 44 reproductive aged women operated because of adnexial masses and revealed pathologic diagnosis’ like endometriosis (Group I; n: 22 cases) and follicular cyst (Group II; n: 22 cases) were enrolled into the study. A semi-quantitative examination of immunohistochemical staining was evaluated as light (+), medium (++) and strong (+++). According to these staining levels, each case was scored as having one, two or three points; and mean scores were calculated for the groups. RESULTS: TGF-ß1, TGF-ß2 and TGF-ß3 staining scores were (48.5±3.1), (25.4±2.3), and (43.7±2.9) in Group I; and (29.2±2.5), (26.5±2.2), and (41.1±3.0) in Group II, respectively. In contrast to the other two isoforms, TGF-ß1’s immunoreactivity was significantly higher in cases with endometriosis (p<0.01). CONCLUSION: Ovarian tissue TGF-ß1 immunoreactivity was significantly increased in endometriosis cases when compared with follicular cyst. There are needed further studies to elucidate the importance of this finding in the pathogenesis of endometriosis.